HIV/AIDS and the long-distance truck drivers in south-west Nigeria: A cross-sectional survey on the knowledge, attitude, risk behaviour and beliefs of truckers (2010)
Objectives: According to the last HIV surveillance survey conducted in 2008, the overall National HIV prevalence in Nigeria stands at 4.6%. Recent studies and estimates by UNAIDS/WHO show higher prevalences in some selected states in Nigeria. The focus of this study is to determine the prevalence, risk behaviour, attitude and knowledge of HIV among long-distance heavy-truckers from a cross sectional survey conducted in the south-west Nigeria. Methods: Four major truck terminals (devoted to long-distance trips) in south western Nigeria were identified. A cross-sectional survey was conducted using a total sample size of 451 truckers who consented to be interviewed. A questionnaire (in English, Hausa and Yoruba languages) for data collection on the socio-demographic, risk behaviour, attitude and knowledge of HIV from the truckers was also designed. The multiple logistic regressions analysis was used to assess the association between some selected variables and factors. Results: Only 164 (36.4%) participants out of the study population of 451 were tested for HIV (due to limited test facilities and consent) and the prevalence of HIV antibodies among the truckers was found to be 2.4% (4/164) with all the infected individuals being within 21—30 years of age. 309 (68.1%) of the respondents admitted that they were at risk of contracting HIV while a total of 249 (55.3%) admitted that they had more than one sexual partners. In addition, while 392 (86.9%) said it was important for them to know their HIV status, 88 (19.5%) said that they would commit suicide should they test positive for HIV.